Problems of Sea Power as we Approach the Twenty-First Century - George, James L.; American Enterprise Institute for Public Policy Research (Washington: American Enterprise Institute for Public Policy Research, 1978)
There are five parts of discussion to this conference publication. Part one discusses Changing naval missions. Part two-Areas of conflict. Part three- The future of sea-based air power. Part four- Balance of the fleet. Part five- The future of the American merchant marine, and sea power and the energy crisis by the guest speakers.
Papers presented at a conference held Oct. 6 and 7, 1977, in Washington, and sponsored by the American Enterprise Institute.
Includes bibliographical footnotes.
ne 17/05/2018
Loan
Keywords: Sea-power; Twenty-first century